Effect of flame heat flux on thermal response and fire properties of char‐forming composite materials. (26th September 2012) - Yu, Ziqing; Zhou, Aixi
SUMMARY This study evaluates the effect of flame heat flux on the prediction of thermal response and fire properties of a char‐forming composite material. A simplified two‐layer flame model was developed and incorporated into a heat transfer thermal model to predict the thermal response and fire reaction characteristics of a burning material. A typical char‐forming material, E‐glass reinforced polyester composite, was used in the study. A cone calorimeter was used to measure the fire reaction characteristics of the composite. The flame heat flux in a cone calorimeter test setup was estimated using the simplified flame model. Thermal response and fire property predictions with and without the effect of flame heat flux were compared with experimental data obtained from the cone calorimeter tests. Results showed that the average flame heat flux of the composite in a cone calorimeter was 19.1 ± 6 kW/m² from model predictions. The flame had a significant effect on the thermal response and fire properties of the composite around the first heat release peak but the effect decreased rapidly afterwards. Copyright © 2012 John Wiley & Sons, Ltd.